Anti-tumor activity of emodin against human chronic myelocytic leukemia K562 cell lines in vitro and in vivo - Chun-Guang, Wang; Jun-Qing, Yang; Bei-Zhong, Liu; Dan-Ting, Jin; Chong, Wang; Liang, Zhong; Dan, Zhu; Yan, Wu (European journal of pharmacology, 2010)
Emodin (1,3,8-trihydroxy-6-methyl-anthraquinone), a natural anthraquinone derivative isolated from Rheum palmatum L, has been reported to exhibit anti-cancer effect on several human cancers such as liver cancers and lung cancers. However, the molecular mechanisms of emodin-mediated tumor regression have not been fully defined. Our preliminary study showed that emodin had highly cytotoxic effect on human chronic myeloid leukemia K562 cell lines. This study was performed to investigate the anti-tumor effect of emodin in human K562 cell line in vitro and in vivo. The MTT data showed the inhibition on growth of K562 cells following emodin treatment. Flow cytometry showed that the cell cycle of K562 cells was arrested in G 0/G 1 phase. Through Western blot analysis, we found that the apoptosis-related protein Bcl-2 was decreased in a dose-dependent manner and the Bax was increased after emodin treatment. Moreover, activations of caspase-3, -8 and -9 were demonstrated in vitro and in vivo. The increased Bax concurrent with the decreased of Bcl-2 indicated that emodin treatment might result in apoptosis of K562 cells. The cell apoptosis was also directly demonstrated by Annexin V-FITC, and DNA fragmentation assay. Additionally, the tumoricidal effect of emodin was measured using a xenograft nude mice model. We found that, after inoculated with the K562 cells, the nude mice treated with emodin showed a significant decrease of tumor volume and tumor weight in comparison to the control. Emodin could cause the regression of tumor. Both in vitro and in vivo studies suggest that emodin can be developed as a promising anti-chronic myeloid leukemia drug.